KATEGORI BERPIKIR KREATIF SISWA KELAS VII SMP NEGERI 1 SURAKARTA DALAM MENYELESAIKAN MASALAH MATEMATIKA PADA MATERI POKOK HIMPUNAN - Masruroh, Rahmawati; Sujadi, Imam; Sari S, Dewi Retno (Jurnal Pembelajaran Matematika, 2015)
Abstract: The purpose of this research was to describe the fluency, flexibility, and novelty of seventh grade students of SMP Negeri 1 Surakarta who have the high, moderate, and low mathematics ability to solve the mathematics problem on the topic of union. This research was qualitative research. The subjects were taken from seventh grade student of SMP Negeri 1 Surakarta. The subjects were 9 students; 3 students with high ability, 3 students with moderate ability, and 3 students with low ability. Data were collected through think aloud method in which students were asked to express what he thought orally. The main data sources were the words and actions of students while being interviewed. Data was validated using data triangulation where data collection was conducted at two different time. The research results showed that the students with the high, moderate, and low mathematics ability had different characteristics in fluency, flexibility and novelty.Keywords: fluency, flexibility, novelty, problems solving.